2019
DOI: 10.1029/2018wr024090
|View full text |Cite
|
Sign up to set email alerts
|

Improving Precipitation Estimation Using Convolutional Neural Network

Abstract: Precipitation process is generally considered to be poorly represented in numerical weather/climate models. Statistical downscaling (SD) methods, which relate precipitation with model resolved dynamics, often provide more accurate precipitation estimates compared to model's raw precipitation products. We introduce the convolutional neural network model to foster this aspect of SD for daily precipitation prediction. Specifically, we restrict the predictors to the variables that are directly resolved by discreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 63 publications
0
128
0
Order By: Relevance
“…The CNN offers a viable tool for precipitation estimation problems since it can gain more abstract and more expressive information from multispectral channels. Recently, a CNN was implemented to estimate precipitation based on the dynamic and moisture fields from numerical weather model analysis (Pan et al 2018). Pan et al (2018) showed that the CNN technique can improve numerical precipitation estimation on the west and east coasts of United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNN offers a viable tool for precipitation estimation problems since it can gain more abstract and more expressive information from multispectral channels. Recently, a CNN was implemented to estimate precipitation based on the dynamic and moisture fields from numerical weather model analysis (Pan et al 2018). Pan et al (2018) showed that the CNN technique can improve numerical precipitation estimation on the west and east coasts of United States.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a CNN was implemented to estimate precipitation based on the dynamic and moisture fields from numerical weather model analysis (Pan et al 2018). Pan et al (2018) showed that the CNN technique can improve numerical precipitation estimation on the west and east coasts of United States. Miao et al (2019) applied a combination of CNN and long short-term memory (LSTM) to improve the resolution and accuracy of precipitation estimates based on dynamical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, CNNs using NWP data as predictors are used to produce either a classification or a pointwise regression, meaning that the CNN produces a zero dimension result from two dimensional data. For example to correct the precipitation forecast integrated over a region, to estimate if a thunderstorm will produce large hailstones, or to predict if a storm will generate a tornado (Pan et al, 2019;Gagne II et al, 2019;Lagerquist et al, 2019a). Few NWP postprocessing using CNNs has been performed on a grid scale.…”
Section: Introductionmentioning
confidence: 99%
“…Effective use of the available big data from multi-sensors is one direction to improve the accuracy of precipitation estimation products [15]. Recent developments of Machine Learning (ML) techniques from the fields of computer science have been extended to the geosciences community and is another direction to improve the accuracy of satellite-based precipitation estimation products [9,[15][16][17][18][19][20][21][22][23]. Deep Neural Networks (DNNs) are a specific type of ML model framework with great capability to handle a huge amount of data.…”
Section: Introductionmentioning
confidence: 99%